Exploring Public Perceptions towards Online Content Regulation in Kenya - Ndanu Mutua, Sylvia (Multidisciplinary Journal of Technical University of Mombasa, 2023)
The rise in illegal online content has necessitated most governments to come up with legislation to regulate the cyberspace environment in their respective jurisdictions. Using an exploratory research design and utilizing a 5-point Likert scale survey (N = 530 Kenyan internet users) the study proposed to highlight the gravity of the public perceptions towards online content regulations in a sub-Saharan African country, with an ever-increasing youthful population. By focusing on the policy-specific factors, the study findings indicated a low public perception of the effectiveness of the existing online content regulations in Kenya. The findings further illustrate a perceived low level of trust in the government agencies responsible for the implementation of these regulations. Taken together, these findings translate to mild acceptability of the existing public policy, indicating a policy perception and acceptance gap that needs to be filled.
Keywords: Content regulation, public policy, public perceptions, online content, Kenya